Clinical nutrition and human rights: an international position paper - Gil Hardy (Indonesian Nutrition Association, 2022)
Worldwide Societies for Clinical Nutrition have launched a promotional campaign that advocates for all patients to have access to food and evidence-based artificially administered nutrition and hydration (AANH). The campaign is supported by the simultaneous publication of a major position paper in, Clinical Nutrition and Nutrition in Clinical Practice, the official journals of the European and North American professional societies. The working group of experts in human rights and clinical nutrition, includes representatives of the American Society for Enteral and Parenteral Nutrition (ASPEN), The European Society for Clinical Nutrition and Metabolism (ESPEN), Latin American Federation of Nutritional Therapy, Clinical Nutrition and Metabolism (FELANPE), Parenteral and Enteral Nutrition Society of Asia (PENSA) and the West African Society of Parenteral and Enteral Nutrition (WASPEN).